Monotonic and Cyclic Lateral Load Tests on Monopod Winged Caisson Foundations in Sand. Issue 6 (2nd December 2019) - Faizi, Koohyar; Faramarzi, Asaad; Dirar, Samir; Chapman, David
Abstract : Existing caisson foundations, utilised for offshore wind turbines, are required to resist significant lateral loads and overturning moments generated by wind and currents. This paper presents an innovative type of foundation, a "winged caisson foundation", to support offshore wind turbines, which has the ability to provide a larger overturning capacity compared with standard caisson designs. Through a series of small-scale experiments at 1g conditions, the competence of the proposed foundations was examined. Different models with various wing sizes and different soil densities were tested in the laboratory under overturning loadings and the results were compared with a standard caisson. The moment-rotation performance of the foundation under both monotonic and cyclic loading were examined to assess the potential benefits of adding wings to caisson foundations. The results showed that there is a significant increase (up to 75%) in overturning capacity provided by the novel foundation, demonstrating its great potential over standard caissons for their use in offshore wind turbine foundations.